High surface area diamond-like carbon electrodes grown on vertically aligned carbon nanotubes. (February 2015) - Zanin, H.; May, P.W.; Harniman, R.L.; Risbridger, T.; Corat, E.J.; Fermin, D.J.
Abstract: Electrochemically active diamond-like carbon (DLC) electrodes featuring high specific surface area have been prepared by plasma-enhanced chemical vapour deposition (CVD) onto densely packed forests of vertically aligned multiwall carbon nanotubes (VACNTs). The DLC:VACNT composite film exhibits a complex topography with web like features and ridges generated by partial coalescence of the DLC over the CNT arrays. DLC:VACNT electrodes exhibit low background responses over a large potential window, low uncompensated resistance, as well as low charge-transfer impedance in the presence of ferrocyanide as a redox probe. The interfacial capacitance associated with the DLC:VACNT electrode is in the range of 0.6 mF cm −2, a value two orders of magnitude larger than in conventional flat carbon electrodes. DLC films grown onto single-crystal Si(1 0 0) under identical conditions resulted in essentially insulating layers. Conducting-atomic force microscopy studies reveal that the film electro-activity does not arise from specific topographic features in the highly corrugated film. The ensemble of experimental results suggests that the enhanced electrochemical responses are not connected to areas in which the CNT support is exposed to the electrolyte solution. This is remarkable behaviour considering that no dopants have been included during the DLC film growth.